2014
DOI: 10.1002/jbm.b.33271
|View full text |Cite
|
Sign up to set email alerts
|

Properties and fibroblast cellular response of soft and hard thermoplastic polyurethane electrospun nanofibrous scaffolds

Abstract: Soft and hard thermoplastic polyurethane (TPU) and their blends were electrospun to fabricate nanofibrous scaffolds with various properties in order to investigate the substrate property effects on cellular response. The scaffolds were characterized with Fourier transform infrared spectroscopy, thermogravimetric analysis, scanning electron microscopy, water contact angle tests, and protein absorption tests. It was found that the hard segment content in the scaffold increased with the hard TPU ratio, which resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 43 publications
2
30
0
Order By: Relevance
“…Furthermore, GTR/GBR membranes need to display appropriate stiffness to withstand cell attachment and proliferation; otherwise, the membranes may not be clinically useful [4, 7, 9, 12]. A recent study demonstrated that cell viability and proliferation of 3T3 fibroblasts cultured on stiffer membranes were higher than on softer ones [45]. Findings from another investigation showed that the increase in elastic modulus obtained with the incorporation of alginate in a PCL-based membrane resulted in improved cell viability, as well as other important cell activity parameters (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, GTR/GBR membranes need to display appropriate stiffness to withstand cell attachment and proliferation; otherwise, the membranes may not be clinically useful [4, 7, 9, 12]. A recent study demonstrated that cell viability and proliferation of 3T3 fibroblasts cultured on stiffer membranes were higher than on softer ones [45]. Findings from another investigation showed that the increase in elastic modulus obtained with the incorporation of alginate in a PCL-based membrane resulted in improved cell viability, as well as other important cell activity parameters (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The morphology of electrospun fibers can be controlled to match the desired structure and orientation by altering the working parameters—including solution properties, processing variables, and ambient conditions—and the types of fiber collector . For instance, to produce tubular grafts composed of circumferentially aligned fibers, one can use a rotating rod to gather the fibers; this method has been employed in certain studies before . However, how to safely remove electrospun samples from a collecting mandrel without causing structural damage has been the main challenge for rod‐type collectors.…”
Section: Introductionmentioning
confidence: 98%
“…[32][33][34] For instance, to produce tubular grafts composed of circumferentially aligned fibers, one can use a rotating rod to gather the fibers; this method has been employed in certain studies before. [35][36][37][38][39][40][41][42] However, how to safely remove electrospun samples from a collecting mandrel without causing structural damage has been the main challenge for rod-type collectors. Also, a crimped fibrous architecture is an important factor for providing vascular grafts with similar non-linear stress-strain behavior comparable to native blood vessels.…”
Section: Introductionmentioning
confidence: 99%
“…TPU blends are used in specialized biomedical applications like artificial cardiovascular components, skin and bone regeneration, and targeted drug delivery . PDMS is another class of material which is growing in tandem with TPU in terms of biological applications due to its unique biocompatibility .…”
Section: Introductionmentioning
confidence: 99%